(untitled) (Applied Biological Research, 2024)
Phytochemicals are widely being explored for their cancer preventive properties in today’s oncotherapy. Quercetin is a major constituent of various dietary products and its anti-cancer potential was explored on different cancer cell lines. The present study was conducted to find out the anti-proliferative effects of quercetin on human triple negative breast cancer cell line MDA-MB The anti-cancer potential of quercetin, nano-quercetin and doxorubicin at various concentrations were assessed by cellular cytotoxicity (MTT) assay. The IC50 values of quercetin, nano-quercetin and doxorubicin on MDA-MB 231 cell line were 394.8, 204.6 and 17.17 μM, respectively. In vitro anti-cancer effects of these drugs were manifested as apoptosis and cellular toxicity. The cytotoxicity was moderate in quercetin, remarkable in nano-quercetin and strong in doxorubicin treatments. The in vitro anti-cancer effect of quercetin was comparable with the standard drug doxorubicin. Considering the potential side effects of doxorubicin, the quercetin might be explored with further studies in the treatment of mammary tumours in animals and humans.